Chemotherapeutic Role of Polyphenols Present in Ocimum sanctum - Khatoon, Saima; Kalam, Nida; Balasubramaniam, Vinod R.; Shaikh, Mohd. Farooq; Ansari, Mohammad Tahir (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Ocimum sanctum is a sacred herb of India and is commonly known as ‘Tulsi’ or ‘Holy Basil’ in regional languages of the country. Various parts of O. sanctum are recognised to have remarkable therapeutic efficacy, and are therefore used in Indian traditional medicine system, Ayurveda. Scientific studies have shown that O. sanctum has a range of pharmacological activities. The presence of a substantial amount of polyphenols in O. sanctum could be the reason for its excellent bioactivity. Polyphenols are used to prevent or treat oncologic diseases due to their anti-cancer effects, which are related to activation of apoptotic signaling, cell cycle arrest, binding ability with membrane receptors, and potential effects on immunomodulation and epigenetic mechanisms. The poor bioavailability of polyphenols restricts their clinical use. The application of nanonization has been implemented to improve their bioavailability, penetrability, and prolong their anticancer action. The present review analyses the recent preclinical studies related to the chemo-preventive and therapeutic potential of polyphenols present in O. sanctum. Moreover, the current article also examines in-depth the biochemical and molecular mechanisms involved in the antineoplastic actions of the considered polyphenols.
Keywords: apigenin